Reproducibility of the effects of theta burst stimulation on motor cortical plasticity in healthy participants - Vernet, Marine (2013)
OBJECTIVE: Theta-burst stimulation (TBS) is a repetitive transcranial magnetic stimulation (TMS) protocol, capable of enhancing or suppressing the amplitude of contralateral motor-evoked potentials (MEP) for several minutes after stimulation over the primary motor cortex. Continuous TBS (cTBS) produces a long-term depression (LTD)-like reduction of cortical excitability. The purpose of this study was to assess the test–retest reproducibility of the effects of cTBS and to investigate which neurophysiologic markers of cTBS-induced plasticity are most reproducible. METHODS: In ten healthy participants we evaluated in two different sessions the effects of cTBS (using AP–PA current direction, opposite to most commercial rTMS stimulators) on MEPs induced by single-pulse suprathreshold TMS (using AP–PA or PA current direction) over left motor cortex in the first dorsal inter-osseus (FDI) muscle. RESULTS: Results demonstrate that the marker of cTBS induced-plasticity with highest within-subject reproducibility is the modulation of corticospinal excitability measured 5 min after cTBS. CONCLUSION: Overall the effects of cTBS modulation show limited test–retest reproducibility and some measures of the cTBS effects are more reproducible than others. SIGNIFICANCE: Studies comparing cTBS effects in healthy subjects and patients need to proceed with care. Further characterization of the effects of TBS and identification of the best metrics warrant future studies.